Extracellular HSP90α promotes cellular senescence by modulating TGF‐β signaling in pulmonary fibrosis. Issue 8 (28th July 2022) - Zhong, Wenshan; Chen, Weimou; Liu, Yuanyuan; Zhang, Jinming; Lu, Ye; Wan, Xuan; Qiao, Yujie; Huang, Haohua; Zeng, Zhaojin; Li, Wei; Meng, Xiaojing; Zhao, Haijin; et al.
Abstract: Recent findings suggest that extracellular heat shock protein 90α (eHSP90α) promotes pulmonary fibrosis, but the underlying mechanisms are not well understood. Aging, especially cellular senescence, is a critical risk factor for idiopathic pulmonary fibrosis (IPF). Here, we aim to investigate the role of eHSP90α on cellular senescence in IPF. Our results found that eHSP90α was upregulated in bleomycin (BLM)‐induced mice, which correlated with the expression of senescence markers. This increase in eHSP90α mediated fibroblast senescence and facilitated mitochondrial dysfunction. eHSP90α activated TGF‐β signaling through the phosphorylation of the SMAD complex. The SMAD complex binding to p53 and p21 promoters triggered their transcription. In vivo, the blockade of eHSP90α with 1G6‐D7, a specific eHSP90α antibody, in old mice attenuated the BLM‐induced lung fibrosis. Our findings elucidate a crucial mechanism underlying eHSP90α‐induced cellular senescence, providing a framework for aging‐related fibrosis interventions.